Perception of the Most Esthetically Pleasing Incisal Embrasure Design - Amina Badshah; Mariya Khalid (Gandhara University, 2022)
OBJECTIVES: To determine the frequency of female dentate patients' most appealing incisal edge embrasure designs. METHODOLOGY: The sample consisted of 385 female dentate patients between 18 to 40 years of age visiting Sardar Begum Dental College and Hospital, Peshawar, from January 2021 to June 2021. The subject's perception was recorded by having the subjects visualize a set of five photographs showing different categories of incisal edge embrasure designs classified by Foulger and Tredwin. The labels of these different photograph categories were obscured using a non-transparent tape, and A, B, C, D, and E; names were assigned to them, respectively, to avoid bias. Means and standard deviations were calculated for quantitative variables like age, while the frequency was calculated in percentage for categorical variables for the most appealing incisal edge embrasure design. RESULTS: The most attractive incisal edge embrasure design amongst the female dentate patients was the "Ideal" design with 33.8%. The second most attractive design displayed "Equal" incisal edge embrasures with 31.4. The "Reversed" and "None" categories had 12.2% and 9.9% percentages. The least attractive design amongst these females was with "Exaggerated" incisal edge embrasures. CONCLUSION: Female dentate patients' most appealing incisal edge embrasure design displays the "Ideal" incisal edge embrasure form.